Greed and Corporate Failure - Hamilton, S., Micklethwait, A. (New York Palgrave macmillan, 2006)
This book is not about stock market "bubbles". Nor is it about accounting scandals and craven auditors. Rather, its about why companies fail.
Keywords: Science